Adsorption and Desorption of Nickel (II) Ion by Oil Palm Empty Fruit Bunch grafted Polyvinyl Alcohol Hydrogel - Rafeek, M.R. (2019)
Oil palm empty fruit bunch grafted polyvinyl alcohol (OPEFB-g-PVA) hydrogel was prepared for the removal of Nickel (II) ions in wastewater. OPEFB-g-PVA was synthesized using ammonium persulfate (APS) as the initiator and boric acid as the crosslinking agent via solution polymerization. Atomic absorption spectroscopy (AAS) was used to determine Ni (II) adsorption properties and scanning electron microscope (SEM) was used to study the morphology. Langmuir and Freundlich isotherms were used to analyse the adsorption mechanism. The most efficient hydrogel in Ni (II) adsorption was obtained at 15 wt OPEFB-g-PVA hydrogel as the concentration of Ni (II) reduced from 10 mg/g to 7.00 Â± 0.02 mg/g with the highest water absorbency capacity at 134 g/g. For desorption of Ni (II), 20 wt OPEFB-g-PVA hydrogel shows the highest amount of Ni (II) desorption concentration of 2.48 mg/g. The adsorption isotherms fit the linear Langmuir isotherm model for OPEFB filled hydrogels. This low-cost sorbent based OPEFB proved to have a great future potential in wastewater treatment. Copyright Â© 2019, AIDIC Servizi S.r.l.